2023
DOI: 10.3389/fbioe.2023.1153631
|View full text |Cite
|
Sign up to set email alerts
|

Role of BMP-7 on biological parameters osseointegration of dental implants: Preliminary results of a preclinical study

Abstract: The aim of this work was to analyze and compare the effect of bone morphogenetic protein-7 on biological parameters related to implant osseointegration in an experimental animal model. Sixteen dental implants were placed in the tibias of four randomly selected minipigs for the following dental implant surface treatments: Group A: conventional treatment of the dental implant surface by SLA (n = 8) and Group B: treatment of the dental implant surface with carboxyethylphosphonic acid and bone morphogenetic protei… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 54 publications
(58 reference statements)
0
2
0
Order By: Relevance
“…The surface functionalization with rmBMP-7 likely causes a burst release of the exogenous growth factor, providing an extracellular BMP-7 concentration within the range that has been shown to be inhibitory for osteogenic differentiation [ 26 , 27 , 28 ]. However, this simple functionalization strategy must be considered with caution in light of other successful ones using either minimal or much higher concentrations of BMP-7 [ 8 , 9 , 10 , 11 ] On the other hand, it permits estimating the challenges that arise when one tries to mimic the interfacial in vivo reality for the design of in vitro studies on cell response to organic coatings on Ti. Our results highlight that it is feasible to evaluate the interactions of pre-osteoblastic cells with a Ti surface, and likely those with other solid biomaterials, and more closely mimic the in vivo reality by integrating a physiological blood clot prior to cell culture.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The surface functionalization with rmBMP-7 likely causes a burst release of the exogenous growth factor, providing an extracellular BMP-7 concentration within the range that has been shown to be inhibitory for osteogenic differentiation [ 26 , 27 , 28 ]. However, this simple functionalization strategy must be considered with caution in light of other successful ones using either minimal or much higher concentrations of BMP-7 [ 8 , 9 , 10 , 11 ] On the other hand, it permits estimating the challenges that arise when one tries to mimic the interfacial in vivo reality for the design of in vitro studies on cell response to organic coatings on Ti. Our results highlight that it is feasible to evaluate the interactions of pre-osteoblastic cells with a Ti surface, and likely those with other solid biomaterials, and more closely mimic the in vivo reality by integrating a physiological blood clot prior to cell culture.…”
Section: Discussionmentioning
confidence: 99%
“…Bone morphogenetic protein 7 (BMP-7) has been used in functionalization studies of biomaterials, due to its recognized stimulatory effects on osteogenic activity under specific conditions and the permission for its use in humans by the Food and Drug Administration [ 8 , 9 ]. The strategies used to functionalize with BMP-7 involve modifications of the biomaterial surface chemistry and topography at a nanoscale, including those of metals [ 8 , 9 , 10 , 11 ]. In a previous initial study, we observed that the effects of providing 40 and 200 ng/mL of a recombinant mouse (rm) BMP-7 to osteoblastic cells grown on titanium (Ti) were modulated by the nanotopographic features of its surface, with an increased expression of the osteoblast markers osteopontin (OPN) and alkaline phosphatase (ALP), but without enhancement in the mineralized matrix formation [ 12 ].…”
Section: Introductionmentioning
confidence: 99%